A Fully Flexible Intelligent Thermal Touch Panel Based on Intrinsically Plastic Ag2S Semiconductor - Zhao, Xue‐Feng; Yang, Shi‐Qi; Wen, Xiao‐Hong; Huang, Qi‐Wei; Qiu, Peng‐Fei; Wei, Tian‐Ran; Zhang, Hao; Wang, Jia‐Cheng; Zhang, David Wei; Shi, Xun; Lu, Hong‐Liang (Advanced materials (Weinheim), 2022)
Wearable touch panels, a typical flexible electronic device, can recognize and feed back the information of finger touch and movement. Excellent wearable touch panels are required to accurately and quickly monitor the signals of finger movement as well as the capacity of bearing various types of deformation. High‐performance thermistor materials are one of the key functional components, but to date, a long‐standing bottleneck is that inorganic semiconductors are typically brittle while the electrical properties of organic semiconductors are quite low. Herein, a high‐performance flexible temperature sensor is reported by using plastic Ag2S with ultrahigh temperature coefficient of resistance of −4.7% K−1 and resolution of 0.05 K, and rapid response/recovery time of 0.11/0.11 s. Moreover, the temperature sensor shows excellent durability without performance damage or loss during force stimuli tests. In addition, a fully flexible intelligent touch panel composed of a 16 × 10 Ag2S‐film‐based temperature sensor array, as well as a flexible printed circuit board and a deep‐learning algorithm is designed for perceiving finger touch signals in real‐time, and intelligent feedback of Chinese characters and letters on an app. These results strongly show that high‐performance flexible inorganic semiconductors can be widely used in flexible electronics. A fully flexible intelligent thermal touch panel based on the intrinsically plastic Ag2S semiconductor can well perceive finger touch signals in real‐time and displays intelligent feed back of Chinese characters and letters on an app.